2017
DOI: 10.1016/j.drugalcdep.2017.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral immune factors are elevated in women with current or recent alcohol dependence and associated with altered mood and memory

Abstract: Background The adverse effects of alcohol on brain function result, in part, from inflammatory processes. The sex-specific neuropsychiatric consequences and inflammatory status of active alcohol dependence and early remission from dependence have not been investigated. Methods Neuropsychiatric symptoms, inflammatory factors, and liver enzymes were compared in a prospective cohort study of adults with (n = 51) or without (n = 31) a current or recent history of alcohol dependence. Results Neuropsychiatric pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 57 publications
0
13
1
Order By: Relevance
“…Lastly, there were only four women with a history of MA dependence in this study, thereby limiting our power to examine the interactive effects of sex. A growing literature, however, highlights sex differences in drug use behavior (52), and we recently reported that in alcohol use disorder, there are sex differences in the effects of alcohol use history on peripheral immune-related factors [i.e., tissue inhibitor of metalloproteinase 1 (TIMP-1) and brain derived neurotrophic factor (BDNF)] (53). Future studies with more women with MA use disorder are warranted to determine the mechanisms by which inflammation may interact with sex.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, there were only four women with a history of MA dependence in this study, thereby limiting our power to examine the interactive effects of sex. A growing literature, however, highlights sex differences in drug use behavior (52), and we recently reported that in alcohol use disorder, there are sex differences in the effects of alcohol use history on peripheral immune-related factors [i.e., tissue inhibitor of metalloproteinase 1 (TIMP-1) and brain derived neurotrophic factor (BDNF)] (53). Future studies with more women with MA use disorder are warranted to determine the mechanisms by which inflammation may interact with sex.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated alcohol-mediated neurotoxic insults may compromise the innate immune response or result in complex compensatory and neuroadaptive processes that limit neuroinflammation. Individual differences such as age and sex, however, are important factors in the neuroimmune response (Pascual et al, 2017;Wilhelm et al, 2017), and more studies are needed to better identify the mechanisms by which alcohol use affects immune signaling.…”
Section: Alcoholmentioning
confidence: 99%
“…Wilhelm et al (31) investigated plasma levels of the pro-inflammatory compound tissue inhibitor of metalloproteinases (TIMP-1) and found them to be associated to self-reported memory complaints in a small sample of female (but not male) alcohol-dependent patients.…”
Section: Resultsmentioning
confidence: 99%